2019
DOI: 10.1177/1526602819828377
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Suitability of Ruptured Abdominal Aortic Aneurysms for Total Endovascular Repair Using the Endurant Endograft and Heli-FX EndoAnchors

Abstract: Purpose: To assess if the suitability of endovascular aneurysm repair (EVAR) of ruptured abdominal aortic aneurysms (RAAAs) can be expanded by combining the Endurant stent-graft with the Heli-FX EndoAnchors. Materials and Methods: Contrast-enhanced computed tomography (CT) scans of 90 patients (mean age 73.2±9 years; 87 men) with RAAA admitted between January 2014 and January 2018 in 2 tertiary care centers were analyzed in a 3-dimensional workstation. Anatomical features of the aneurysms according to the inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Within its evidence review is the non-randomized IMPROVE trial, which suggests that EVAR under LA for RAAA may have lower short-term mortality than EVAR under GA [18]. In a recent review of CT scans of 90 patients with RAAA, of the 46 patients who were unsuitable for conventional EVAR, 24 could have been treated with ESAR, an absolute increase of 27% [7]. Regardless of the long-term role of EAs, LA-ESAR could be applied to these patients with RAAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within its evidence review is the non-randomized IMPROVE trial, which suggests that EVAR under LA for RAAA may have lower short-term mortality than EVAR under GA [18]. In a recent review of CT scans of 90 patients with RAAA, of the 46 patients who were unsuitable for conventional EVAR, 24 could have been treated with ESAR, an absolute increase of 27% [7]. Regardless of the long-term role of EAs, LA-ESAR could be applied to these patients with RAAA.…”
Section: Discussionmentioning
confidence: 99%
“…However, EVAR provides better outcomes than open surgical repair (OSR) in ruptured AAA (RAAA), with a potentially increased benefit if EVAR is performed under local anesthesia (LA) [ 6 ]. It has been postulated that ESAR might expand the indications of EVAR among patients with RAAA [ 7 ]. Therefore, it is essential to be able to achieve ESAR without general anesthesia (GA), as the ability to perform the procedure under LA is an advantage of EVAR over OSR.…”
Section: Introductionmentioning
confidence: 99%
“…ESAR should not be considered a competitive but indeed a complementary technique that is both useful and accessible/available when hostile neck anatomic features are encountered, and correct technical deployments are accomplished, 4,29 avoiding potential complications of other complex techniques. 30,31 We aim to keep data inclusion open for all centers that want to participate on this multicenter collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, the device has been removed from the market. Reyes Valdivia et al demonstrated that the suitability of EVAR of rAAA can be expanded by combining the Endurant stent-graft with the Heli-FX EndoAnchors and Galinanes et al used such EndoAnchors to minimize endoleaks in chimney-graft endovascular repair of juxtarenal AAA [168,169]. However, Goudeketting revealed that almost 30% of EndoAnchors had been maldeployed outside of the recommended use [170].…”
Section: Novel Strategiesmentioning
confidence: 99%